Protection of long-term land ownership: some problematic aspects - Yu. I. Chalyi (Bulletin of Kharkiv National University of Internal Affairs)
The ability of Ukrainian current legislation and law enforcement practice to provide effective protection of the interests of titleless bona fide landowners was critically assessed. It is noted that the problems of the long-term owners’ interests protection should be solved in the scope of a more general problem, namely the protection of titleless ownership as such. Emphasis is placed on the need for autonomous formulation in the Civil Code of Ukraine of provisions on the protection of titleless ownership and possession of property based on law. This is due to the fact that these civil law institutions have a very different legal nature. The description of these institutions in the national legislation of Ukraine is highlighted, which will take into account the specifics of the legal regulation of relations on the actual ownership of property and increase the effectiveness of protection of the interests of titleless owners. The position of the highest courts of Ukraine on the extension of the regime of protection of real subjective rights to long-term ownership has been challenged. Attention is paid to the need for scientific substantiation of legislative expansion of the methods of protection of long-term land ownership. The current legislation of Ukraine allows the possibility of protecting the interests of long-term landowners only by filing a lawsuit to restore their de facto control over such property. Ways to protect against non-loss of property are not legally available to long-term landowners. It is emphasized that the possibility of satisfying the claims of the long-term owner to restore possession of the property must be linked to the condition of good faith conduct of such a plaintiff. The good faith conduct of the owner should be considered both at the time of establishment of possession and in relation to the subsequent circumstances of possession of the property. In particular, the owner of the property may know that he or she does not have a title to the property and even know who owns the property, but if the owner does not hide the fact of taking someone else's property and is willing to return the property to its owner, it should be considered bona fide.